Environmental and Occupational Pollutants and Their Effects on Health among Brick Kiln Workers - Sanjel, Seshananda; Thygerson, Steven M.; Khanal, Sanjay N.; Joshi, Sunil Kumar (Scientific Research, 2016)
The ever expanding traditional brick industry in Nepal is a labour intensive, low technology activity found in the Kathmandu Valley and Terai regions of Nepal. While environmental pollutants associated with brick making have been characterized, the effects of these pollutants on the workers themselves have received relatively little attention. This review attempts to summarize and interpret the available recent evidences characterizing the extent of exposure to risk factors and health problems of brick kiln workers.
Keywords: Brick Kiln Emission; Occupational Exposure; Respiratory Problems; Musculoskeletal Disorders